The Influence of Attention, Relevance, Confidance, and Satisfaction (ARCS) Learning Model on Science Learning Outcomes of Fifth Grade Elementary School Students: Pengaruh Model Pembelajaran Attention, Relevance, Confidance, and Satisfaction (ARCS) Terhadap Hasil Belajar IPA Siswa Kelas V SD - Ahmad Bahri; Supriyadi Supriyadi (Academia Open, 2021)
Learning strategies and learning models will continue to be updated in every era. Adjust to the character of the students. This study has a specific purpose, namely to determine whether there is an effect of the ARCS Attention, Relevance, Confidance, and Satisfaction learning model on the science learning outcomes of fifth grade students at SDN Sidokare 1 Sidoarjo. This study uses a Pre-Experimental Design type One-Group Pretest Posttest Design. The population in this study was class V at SDN Sidokare 1 for the academic year 2020/2021 with 20 students. The instrument used in measuring students' interest in learning is a questionnaire. This study uses descriptive statistics and inferential statistics in testing the data with t-test and eta-squared to test the research hypothesis.